STRATEGI GURU AGAMA DALAM PEMBINAAN AKHLAKUL KARIMAH SANTRI DI PONDOK PESANTREN AR-RAHMAH BANTUR MALANG - Fika Salamah; Muhammad Odik Afifin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Education in good character is an important foundation in Islamic education because it plays a role in shaping the personalities of students in line with Islamic values amid the moral challenges of the modern era. This study aims to examine the strategies used by religious teachers in instilling good character in students at the Ar-Rahmah Islamic Boarding School in Bantur, Malang, including the forms of strategy, the implementation process, student responses, and the dynamics of behavioral change. The study is based on the theory of Islamic moral education, which emphasizes role modeling, habit formation, wise advice, and humanistic pedagogical relationships. The research uses a descriptive qualitative approach through semi-structured interviews and direct observation, then analyzed through data reduction, data presentation, and conclusion drawing through source and technique triangulation. The results of the study show that the main strategies include teacher role modeling, habituation of pesantren activities, a personal approach, persuasive advice, and educational sanctions. These strategies instill the values of ta'dzim, discipline, social awareness, mutual respect, and obedience to rules.